Duration and intensity of shade differentially affects mycorrhizal growth- and phosphorus uptake responses of Medicago truncatula - Konvalinková, Tereza; Püschel, David; Janoušková, Martina; Gryndler, Milan; Jansa, Jan (Frontiers in Plant Science, 2015)
Plant and fungal partners in arbuscular mycorrhizal (AM) symbiosis trade mineral nutrients for carbon, with the outcome of this relationship for plant growth and nutrition being highly context-dependent and changing with the availability of resources as well as with the specific requirements of the different partners. Here we studied how the model legume Medicago truncatula, inoculated or not with a mycorrhizal fungus Rhizophagus irregularis, responded to a gradient of light intensities applied over different periods of time, in terms of growth, phosphorus nutrition and the levels of root colonization by the mycorrhizal fungus. Short-term (6 d) shading, depending on its intensity, resulted in a rapid decline of phosphorus uptake to the shoots of mycorrhizal plants and simultaneous accumulation of phosphorus in the roots (most likely in the fungal tissues), as compared to the non-mycorrhizal controls. There was, however, no significant change in the levels of mycorrhizal colonization of roots due to short-term shading. Long-term (38 d) shading, depending on its intensity, provoked a multitude of plant compensatory mechanisms, which were further boosted by the mycorrhizal symbiosis. Mycorrhizal growth- and phosphorus uptake benefits, however, vanished at 10% of the full light intensity applied over a long-term. Levels of root colonization by the mycorrhizal fungus were significantly reduced by long-term shading. Our results indicate that even short periods of shade could have important consequences for the functioning of mycorrhizal symbiosis in terms of phosphorus transfer between the fungus and the plants, without any apparent changes in root colonization parameters or mycorrhizal growth response, and call for more focused research on temporal dynamics of mycorrhizal functioning under changing environmental conditions.